Integrated analysis of microbe-host interactions in Crohn's disease reveals potential mechanisms of microbial proteins on host gene expression - Sudhakar, Padhmanand; Andrighetti, Tahila [UNESP]; Verstockt, Sare; Caenepeel, Clara; Ferrante, Marc; Sabino, João; Verstockt, Bram; Vermeire, Severine (Elsevier, 2022)
Inflammatory responses of the intestinal epithelial barrier in patients with Crohn's disease (CD), a chronic inflammatory bowel disease (IBD), are associated with gut microbial alterations. At a community level, there is scarce mechanistic evidence on the effects of gut microbial alterations on host mucosal barrier responses. We used a computational microbe-host interaction prediction framework based on network diffusion and systems biology to integrate publicly available paired gut microbial and intestinal gene expression datasets. The ileal signaling network potentially modulated by the microbiota was enriched with immune-related pathways such as those associated with IL-4, IL-2, IL-13, NFkB, and toll-like receptors. We identified bacterial proteins eliciting post-translational modifications on host receptors, resulting in the de-repression of pro-inflammatory cytokines via critical hub proteins such as NFkB. The signaling networks were over-represented with CD associated genes and CD drug targets. Using datasets generated from our validation cohorts, we confirmed some of the results.
Keywords: Gastroenterology; Microbiome; Molecular genetics